Influence Of Gender Of The Board Of Directors On Firm Performance With The Intensity Of Innovation As Moderate Variable - Hidayati Nur Rochmah; Hayyu Rachma Annisa; Wisudanto Mas Soeroto (Universitas Katolik Indonesia Atma Jaya, 2021)
ABSTRACT This study aims to examine the role of innovation intensity in moderating the influence of board gender on company performance. This study uses quantitative data with data sources in secondary data, which will be processed using SPSS 22 software. This study's population are non-financial companies listed on the Indonesia Stock Exchange for the period 2014-2018 with 690 observations. This study found that board diversity has a positive effect on company performance. The higher the level of board diversity in this case the gender in a board, the higher the level of firm performance. The gender of the board of directors can help in making decisions because there are different perspectives on the discussion. Different perspectives will create a sense of caution which can help prevent risks. Besides, this study also found that the intensity of innovation could strengthen or moderate the effect of board diversity on firm performance. The company's intensity of innovation is higher when there are women on its board of directors. This is because various perspectives are important to be able to provide creative solutions, such as innovation. The intensity of innovation can increase when there is gender diversity on the board of directors to make firm performance increase.